Incidental Finding of an Aorto-Right Atrial Fistula in a Patient Undergoing Repair of a Sinus of Valsalva Aneurysm - Rosero-Britton, Byron R.; Nguyen, Anthony; Warsame, Ibrahim; Shabsigh, Muhammad; Dong, Luke; Wolfe, James; Whitson, Bryan; Essandoh, Michael (Frontiers in Medicine, 2017)
A sinus of Valsalva aneurysm is a rare malformation of the aortic root that can fistulize to another cardiac structure such as the right atrium. Although transthoracic echocardiography and computed tomography angiography have demonstrated utility for the diagnosis of a sinus of Valsalva-to-right atrial fistula, there are few cases where a misdiagnosis may occur. Intraoperative transesophageal echocardiography may be an essential imaging tool for the diagnosis and management of incidental findings such as a sinus of Valsalva-to-right atrial fistula during cardiac surgery, and should be used routinely.